Beyond the glass ceiling: does gender matter? - Adams, Renée; Funk, Patricia (Barcelona, 2009)
"The representation of women in top corporate officer positions is steadily increasing. However, little is known about the impact this will have. A large literature documents that women are different from men in their choices and in their preferences, but most of this literature relies on samples of college students or workers at lower levels in the corporate hierarchy. If women must be like men to break the glass ceiling, we might expect gender differences to disappear among top executives. In contrast, using a large survey of all directors of publicly-traded corporations in Sweden, we show that female and male directors differ systematically in their core values and risk attitudes. While certain population gender differences disappear at the director level, others do not. Consistent with the findings for the Swedish population, female directors are more benevolent and universally concerned, but less power-oriented than men. However, they are less traditional and security-oriented than their male counterparts. Furthermore, female directors are slightly more risk-loving than male directors. This suggests that having a women on the board need not lead to more risk-averse decision-making."